Factors affecting non-adherence to the public recommendation of mask use in Bangladesh: a nationwide survey - Islam, Mohammad Aminul; Kibria, Md. Kaderi; Das, Apon; Huq, Md. Monimul (Intelektual Pustaka Media Utama, 2023)
Effective communication plays an important role in any uncertain situation to reduce its risks. The recent coronavirus disease (COVID-19) pandemic has created uncertainties in human lives around the world. Although infection and deaths rates are decreasing, the need for protective measures and the risk of affecting people by the virus remains high. Moreover, experts recommend that people wear face masks in public places despite vaccination. Evidence shows that people in different parts of the world tend not to use face masks in public places, and Bangladesh is no exception to this phenomenon. Little is known about the topic from the context of the country. In this study, we explored the factors that influence people for non- adherence to the public recommendation of using face masks in public places. We conducted a cross-sectional survey among 1,868 people across the country between March 2021 and December 2021. We used a semi- structured questionnaire to collect the data. The results indicate that the non- adherence to public recommendation for using face masks is associated with people’s age, education, and location of residence; risk perception about the COVID-19; trust in messages from media and public authorities; barriers to effective communication, religious faith, and cost for buying face masks.